Troubleshooting the problems arising from sustainable development. (15th February 2019) - Mikulčić, Hrvoje; Duić, Neven; Schlör, Holger; Dewil, Raf
Abstract: Sustainable development as a concept of societal development encompasses some problems that need to be addressed carefully. They relate to overcoming the technical limits of individual systems, reducing environmental impact, social inclusion, green economic progress involving all stakeholders, limiting the impact of human activities, etc. Over the past few years, as a result of the increasingly pronounced climate change, more and more studies are addressing these problems and stress the importance of sustainable development. The key to sustainable development are, therefore, the solutions to the problems currently encountered by various stakeholders, that together contribute to the preservation of the environment for future generations. This is no longer based on the goodwill of individuals, but has become the responsibility of the entire generation. This article presents some examples of the solutions for the problems arising from sustainable development and is an overview of recent scientific achievements in the field of sustainable development that emerged from recent Sustainable Development of Energy, Water and Environment Systems (SDEWES) conferences. As such, it acts as an editorial paper for the virtual special issue of the Journal of Environmental Management, that is dedicated to the SDEWES2017 conference.